2020
DOI: 10.1186/s13018-020-02097-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and venous thromboembolism after total joint arthroplasty: a meta-analysis of cohort studies

Abstract: Objective Metabolic syndrome (MetS) has been associated with hypercoagulative status. However, previous studies evaluating the association between MetS and incidence of venous thromboembolism (VTE) after total joint arthroplasty (TJA) showed inconsistent results. We performed a meta-analysis to evaluate the influence of MetS on the risk of VTE following TJA. Methods Cohort studies were identified by the search of PubMed, Embase, and the Cochrane’s Library databases. A random-effect model was used if considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previous literature has con rmed that a history of hypertension can increase the risk of VTE after orthopedic surgery [34][35][36]. A metaanalysis of 16 studies involving orthopedic surgical patients (68955 males and 53057 females) reported a signi cant association between hypertension and postoperative DVT (OR = 2.89, 95%CI = 2.18-3.83, P < 0.05, Z = 7.38) [37]. The results of this study suggest that the prevalence of DVT is also signi cantly higher in patients with hypertension prior to joint arthroplasty, and the presumed cause is related to the fact that patients with hypertension are more likely to have disorders of the coagulation system, vascular in ammation, and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…Previous literature has con rmed that a history of hypertension can increase the risk of VTE after orthopedic surgery [34][35][36]. A metaanalysis of 16 studies involving orthopedic surgical patients (68955 males and 53057 females) reported a signi cant association between hypertension and postoperative DVT (OR = 2.89, 95%CI = 2.18-3.83, P < 0.05, Z = 7.38) [37]. The results of this study suggest that the prevalence of DVT is also signi cantly higher in patients with hypertension prior to joint arthroplasty, and the presumed cause is related to the fact that patients with hypertension are more likely to have disorders of the coagulation system, vascular in ammation, and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, cancer is a major cause of death in VTE patients and vice versa. Obesity is associated with a 2‐ to 5‐fold increase in VTE compared to individuals within the normal body mass index range, 59‐61 and similar significant increases in VTE are noted in metabolic syndrome 62‐65 and diabetic patients 66,67 . The relationship between VTE and pathogenic infections has been an area of interest for some years but has jostled to the forefront by way of the COVID‐19 pandemic 68‐71 .…”
Section: Opportunity Areas For Thrombosis and Hemostasis Fundamental ...mentioning
confidence: 99%